PENGARUH PEMAHAMAN MATERI PERJUANGAN BANGSA INDONESIA DALAM MEMPERTAHANKAN KEMERDEKAAN TERHADAP SIKAP NASIONALISME, PATRIOTISM DAN PELESTARIAN NILAI BUDAYA BANGSA - Cheri Saputra; Eddy Purnomo; Maskun Maskun (Faculty of Teacher Training and Education, University of Lampung, 2013)
Socio-cultural resilience in the post-reform has not yet revealed the expected positive changes. This is due to the concept of nationalism which is owned by the citizens are experiencing decline and his figure is not clear. Concept of nationalism that is inclusive and departing from the need felt by citizens will be an important basis for progress of the nation into the coming century is the century globalist.The purpose of this study was to describe the effect is material Understanding the Struggle of Indonesian Independence Defend Against Religious Nationalism, Patriotism and Preservation of Cultural Values Nation On High School Students YP Unila Bandar Lampung in Academic Year 2011/2012. This research method is descriptive correlational, the study sample is class XI Science YP Unila Bandar Lampung totaling 67 people, the data collection techniques used were the tests and questionnaires were then performed statistical analysis of the data processing with SPSS version 17.00.Keywords: learning materials Indonesian national struggle in maintaining independence, the attitude of nationalism, patriotism and attitude preservation of cultural values of the nation